Standardisation of neonatal clinical practice. (11th July 2013) - Bhutta, ZA; Giuliani, F; Haroon, A; Knight, HE; Albernaz, E; Batra, M; Bhat, B; Bertino, E; McCormick, K; Ochieng, R; Rajan, V; Ruyan, P; et al.
Abstract : The International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ) is a large‐scale, population‐based, multicentre project involving health institutions from eight geographically diverse countries, which aims to assess fetal, newborn and preterm growth under optimal conditions. Given the multicentre nature of the project and the expected number of preterm births, it is vital that all centres follow the same standardised clinical care protocols to assess and manage preterm infants, so as to ensure maximum validity of the resulting standards as indicators of growth and nutrition with minimal confounding. Moreover, it is well known that evidence‐based clinical practice guidelines can reduce the delivery of inappropriate care and support the introduction of new knowledge into clinical practice. The INTERGROWTH‐21 st Neonatal Group produced an operations manual, which reflects the consensus reached by members of the group regarding standardised definitions of neonatal morbidities and the minimum standards of care to be provided by all centres taking part in the project. The operational definitions and summary management protocols were developed by consensus through a Delphi process based on systematic reviews of relevant guidelines and management protocols by authoritative bodies. This paper describes the process of developing the Basic Neonatal Care Manual, as well as the morbidity definitions and standardised neonatal care protocols applied across all the INTERGROWTH‐21 st participating centres. Finally, thoughts about implementation strategies are presented.